Biomedical signal processing and modeling in cardiovascular systems - Baselli, Giuseppe; Caiani, Enrico; Porta, Alberto; Montano, Nicola; Signorini, Maria Gabriella; Cerutti, Sergio (Critical reviews in biomedical engineering, 2002)
This article revisits the subject of short-term heart-rate and arterial-pressure variability from the perspective of model structures that can be useful in defining signal processing algorithms. We draw a general scheme of the oscillation sources and interactions that contribute to cardiovascular control mechanisms and highlight the elements that were considered in different modeling works. The origin, superposition, and interaction of respiratory high-frequency (HF) and vasomotor low-frequency (LF) rhythms is presented as the integration of supraspinal and spinal circuits, vasomotor activity, and pressure control loops. We analyze in detail the necessity of considering all relevant interactions for the algorithms designed to estimate the baroreflex sensitivity. We also pinpoint the components of cardiorespiratory coupling in relation to the analysis of data from the acoustic quantification of the left ventricular volume. Finally, we analyze the tendency to produce complex behaviors even in extremely simplified systems involving interactions between oscillatory mechanisms.